Leituras de Obras de Arte na Educação Infantil e suas possibilidades: Projetos com abordagens na natureza - Soares, Samantha Graziele (2023)
This article presents and represents possibilities for proposals, planning, and actions in the classroom in Early Childhood Education, emerging from work with Visual Arts since 2021, in the institutions Benedita Pimentel de Ulhôa Rocha Municipal School and Maria Beatriz Vilela de Oliveira Municipal Elementary School (EMEI) (2021-2022) and Sérgio Aparecido Municipal elementary School (2022-23), located in Uberlândia - MG. Based on a case study research and personal narratives that revealed and discussed teaching-learning, personal experiences as an art teacher. The process of knowledge construction and experiences of children in these schools, reflections, foundations, and interpretations were drawn, reporting the playful ways in which readings of Art in Early Childhood Education could be revealed, based on the theme "Nature". The study aimed to reflect on how image reading can guide experiences and experimentation with nature in Early Childhood Education and enhance Pedagogical Projects, and thus, playful learning, based on contemporary themes (Nature/Environment), of essential importance to be addressed in the current context. From the research of artistic paintings, and the vehement need to take children on a sensory experience beyond the indoor classroom, for contact with the external and natural elements, searches for possibilities in developing Pedagogical Projects based on the Triangular Approach, having image reading as a starting point, together with the elements of nature. The outcome of this research was consolidated with a didactic material for use by the Art teacher, which emerged with the intention of recording the planning and project process, as well as stimulating professionals in this area in relation to the mentioned theme and, thus, connecting child and nature from teaching-learning in Art classes.